Facts and Propositions, Trueman-Style. (31st May 2022) - Sullivan, Peter
Abstract: In a recent book, Robert Trueman develops a version of the identity theory of truth, the theory that true propositions are not in some kind of correspondence with, but are rather identical with, facts. He claims that this theory 'collapses the gap between mind and world'. Whether it does so will obviously depend on how the theory is to be understood, which in turn depends on the argumentative route to it. Trueman's route is clear, rigorous, and free of extravagant assumptions. Perhaps because of those merits it seems obvious that it falls short of the claim he makes for it. But there are difficult questions about the nature of the shortfall and about what in the character of Trueman's philosophical approach prevents him from appreciating it. The paper explores those questions through a comparison with Moore's 'original' identity theory and the Idealist philosophy he directed it against.